Proyecto de factibilidad para la creación de una empresa productora de glucosa de maíz y su comercialización en la ciudad de Loja - Rojas Sànchez, Patricio Alejandro (2016)
The present work of thesis refers to a project of feasibility for the creation of a company producing corn glucose and its commercialization in the producers of bread of the city of Loja, the same one that aims to offer a product of excellent quality and A service that meets the needs of the companies to which we have destined our product. For the development of the present project, it was necessary to use some methods of study, such as: analytical, deductive and inductive, also used techniques such as bibliographic records and the same survey that served to collect information from 80 bread producers surveyed; As well as secondary sources in order to extract relevant information on the requirements necessary for the creation of the feasibility project. In order to determine the feasibility of the project, four studies were carried out: In the Market Study we determined several factors in the sample that are 80 producers of bread provided by the one by the Illustrious Municipality of Loja, the potential demand refers to the 70 bread producers surveyed, of which we determined a per capita consumption of 816gl of maize glucose per year, the real demand is 60 companies producing bread and the effective demand that refers to 55 bread producers being the projection for the first year of 44,880gl of corn glucose; Within the same study we will determine. In calculating the supply we determined a consumption of 8412gl of corn glucose for the first year. Within the market study we also find the marketing plan or marketing mix which is subdivided into five important points that are product, price, place, advertising and promotion. The Technical Study allowed to determine the size and location of the company, which has an installed capacity of 164160gl and a used capacity of 36468gl, of which we will use 75% from the first to fifth year and from the sixth to the tenth year 95% of Its capacity used during the set time. The macro and micro location of the corn glucose plant was determined by the weighting factors that allowed us to determine that the plant location will be located in the city of Loja, on Detroit and Toronto Streets (Industrial Park Located north of The city of Loja). Within this study we also determined everything we need for the start up of the plant such as machinery, tools, computer office equipment etc. Also the flow chart of the stages of the productive process was designed and the study of the facilities was made. The Administrative Study allowed to establish the legal aspects of the company as the constituent minutes and the functional organizational structure ie the hierarchical levels of the company, structural organizational charts, positional and functional organizational of the company and its respective manual of functions. The Financial Study allowed the establishment of fixed assets with a value of $ 26,321.75, Intangible Assets $ 1,290 and current assets or working capital with $ 8,672.41. The financial study also determined the financing that was given through shareholders' own financing and private financing that is from the financial institution of the CFN in the following way 41%, will be contributed by the shareholders of the company, Which will be $ 15,000.00 while 59% of the investment is $ 21,284.16, which will be financed by credit to the CFN, which offers short, medium, long term loans and for our case gave us 10 Years, for the execution of the project at an annual interest rate of 11.5%. With this data we determine the rate of depreciation and then the reinvestments of fixed assets. Finally, we take out the total costs and expenses, then take out the total income to be able to determine the fixed and variable costs with which we will determine the equilibrium points of years number 1.5 and 10. And finally we have the Financial Analysis in which we will determine the net flow, net present value with a value of $ 493,562 which ensures a return on the value of the plant; The internal rate of return of the project is 24.02%, which is why the project is accepted as it is greater than the cost of opportunity of money. The PRC is 4 months and 23 days; The CBR is 1.25 for every dollar invested, which gives us an excellent remuneration; As far as the Sensitivity analysis of the supported project is not sensitive to future alterations either in relation to a 98.15% increase in costs or an increase in costs of 43.63%. In conclusion based on the results obtained in the studies carried out, it is recommended to implement the same, since their profit margins are exponential and are attached to the vision of projecting a company that is going to expand in a very evident way in the Regional south of the country.